1999
DOI: 10.1007/bf03013906
|View full text |Cite
|
Sign up to set email alerts
|

Rectal indomethacin reduces postoperative pain and morphine use after cardiac surgery

Abstract: Rectal indomethacin reduces postoperative pain and morphine use after cardiac surgeryPurpose: To evaluate the combination of rectal indomethacin with patient controlled intravenous morphine analgesia (PCA) on postoperative pain relief and opioid use after cardiac surgery. Methods: With institutional ethics approval, 57 consenting adults undergoing elective aortocoronary bypass surgery were randomly assigned preoperatively in a double-blind fashion to receive either placebo in = 26) or indomethacin 100 mg suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 27 publications
1
32
2
1
Order By: Relevance
“…Our study suggests that in patients free of preoperative renal insufficiency, short-term postoperative naproxen use is not associated with an increased incidence of renal dysfunction following CABG. This is in agreement with other studies that have also found no increased risk of postoperative renal impairment after cardiac surgery in carefully selected patients [12,13].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study suggests that in patients free of preoperative renal insufficiency, short-term postoperative naproxen use is not associated with an increased incidence of renal dysfunction following CABG. This is in agreement with other studies that have also found no increased risk of postoperative renal impairment after cardiac surgery in carefully selected patients [12,13].…”
Section: Discussionsupporting
confidence: 93%
“…The present data add to that of other studies which have also illustrated the analgesic effects of NSAIDs after cardiac surgery. A significant reduction in postoperative pain was demonstrated with the use of ketorolac [9,10], diclofenac [11] and rectal indomethacin after CABG [12]. However, unlike previous trials, this is the first to date to demonstrate an improvement in both pain control and lung function following CABG using a low-cost NSAID such as naproxen.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[20][21][22][23] Therefore, 20 randomized trials (19 papers and one abstract) involving a total of 1,065 patients provided data for this meta-analysis. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Table I outlines the characteristics of included trials. Baseline characteristics of patients are presented in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…A sustained-release suppository can be produced by adding sugar esters to a lipophilic (Witepsol H-15) base [111]. Postoperative indomethacin suppositories (100 mg dosed every 12 h) reduce morphine consumption postoperatively by 38% compared with a placebo control [142].…”
Section: Indomethacinmentioning
confidence: 99%